The Strategy Of The Homeless Survival In Surakarta - Retno Woro Kaeksi; Umrotun Umrotun; Susanto Susanto; Triana Nur Handayani; Satriyo Nugroho (Universitas Muhammadiyah Surakarta, 2002)
The research is carried out in Surakarta. The goal of the study is to know: the characteristic of the homeless, the factors that cause them to he the homeless and the strategis of the homeless to survive in Surakarta. The research uses survey method, while its area is chosen purposively. The research also uses primary and secondary data. The primary data is obtained by interviewing the respondents with questionnaire, while secondary data is based on the information got from the relevant institution.The resjoondents are taken 10 % randomly from all the population. The results of the rsearch show that the homeless are 11-8 years old (96.66%), most of them are boys (91.11%). The majority of the respondents did graduate from the Lower Secondary School (55.56%); most of them come from outside of Surakarta (62%). Their primary activity is as singing beggars (62,22 %) and their daily income is about RP 10. 000 RP 14. 000 (60.00%). Their parents are uneducated people. They are only graduated from Elementary School (7S.56%).The factors that cause them to he homeless are the economic factor 77.78%, lack of family attention (13.33%) and the willingness to he independent (80.89%). Based on the result this research, we know that the poverty has made the children become homeless. The strategis to survive are: they are thrif (40%), add their time to work (13.13%), move to other place (11.11%) and save their money (15.56%).